Engineering Invention & Innovation Exhibition (ENVEX 2009) - Anon (Universiti Malaysia Perlis, 2009)
Organised by School of Environmental Engineering & Student Affairs & Alumni Department in collaboration with Deputy Vice Chancellor Office (Research & Innovation) & Engineering Schools UniMAP